Solve

Guides

0

Question

Open in App

Solution

Verified by Toppr

The negative ratio of focal length of the objective to the focal length of the eyepiece give the focal length of the telescope

$$M=-\dfrac{f_0}{f_{e}}$$

Here, $$f_0$$ is focal length, M is magnification and $$f_e$$ is eyepiece of focal length

Substitute $$2.8$$ cm for $$f_{e}$$, and $$82cm$$ for $$f_0$$

$$M=-\dfrac{82}{2.8}=-29X$$

Substitute $$2.8$$ cm for $$f_{e}$$, and $$82cm$$ for $$f_0$$

$$M=-\dfrac{82}{2.8}=-29X$$

Was this answer helpful?

0